The Church Climate Action: Identifying the Barriers and the Bridges. (July 2020) - Nche, George C
For many decades, efforts are being channelled towards fostering effective robust church-based climate action across the globe. However, this desired action has unfortunately been in short supply. This has been attributed to some factors that serve as barriers to effective church-based climate action. In an extensive review, this article did not only identify these barriers but also the bridges or pathways out of these barriers/challenges. After a critical review of about 150 empirical studies with a few anecdotal literature, findings showed that beyond the theological barriers that are commonly referenced in many studies, the church also faces institutional barriers in their bid to address climate change. The biblical concept of stewardship, climate change awareness/knowledge creation, strategic communication and engagement, and strategic fundraising and mobilisation were found to be the bridges/pathways towards achieving a robust church-based climate action. Implications of findings for the church and research are discussed.